JAMINAN PERLINDUNGAN ANAK KORBAN PERUNDUNGAN DALAM PERSPEKTIF KEADILAN RESTORATIF - Argentum, Crownabe; Sudibya, Komang Pradnyana (Kertha Negara : Journal Ilmu Hukum, 2023)
Children are a state's future and should be treated as such by being safeguarded, protected, and guaranteed to get their rights to life in order to ensure their success as future leaders and contributors to society. Of course, some kids can actually act in ways that disrupt the lives of others their age and even put their lives in danger. As a general rule, this constitutes criminal behavior. Naturally, the resolution of crimes committed by adults and those committed by minors are handled in different ways. Law 11 of 2011 pertaining to the Criminal Justice System for Children addresses the punishment of minors specifically. When dealing with juvenile offenders, restorative justice is used to restore harmony between the juvenile offender and any juvenile victims for the greater good. This, of course, depends on the kindness and cooperation of young victims in diverting criminal cases involving children away from the court system. According to Law Number 11 of 2011 concerning the Criminal Justice System A. - son, this journal discusses the guarantee of protection obtained by child victims in cases of bullying when resolving criminal cases outside of court, or commonly called diversion.